2021
DOI: 10.1101/2021.08.18.21262061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Closed Doors: Predictors of Stress, Anxiety, Depression, and PTSD During the Onset of COVID-19 Pandemic in Brazil

Abstract: Background: The SARS-CoV-2 pandemic first reached Brazil in late February 2020. Since then, it is one of the most affected countries globally. The rise of mental health problems in the population directly or indirectly affected is now a major concern. In the present study, we show the results of the first wave of the COVIDPsiq cohort study, which started early on (April 2020). The aim of this study was to investigate and compare independent predictors of symptoms of stress, anxiety, depression, and post-trauma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Social isolation, among other aspects of the pandemic, may be the catalyst for different mental health consequences (Kim & Bhullar, 2020). For example, Crestani Calegaro et al (2021) reported that two-thirds of their participants felt that their mental health worsened after the onset of social restraint measures. Hyland et al (2020) also reported that generalised anxiety and depression were common in the population during the initial phase of the COVID-19 pandemic.…”
mentioning
confidence: 99%
“…Social isolation, among other aspects of the pandemic, may be the catalyst for different mental health consequences (Kim & Bhullar, 2020). For example, Crestani Calegaro et al (2021) reported that two-thirds of their participants felt that their mental health worsened after the onset of social restraint measures. Hyland et al (2020) also reported that generalised anxiety and depression were common in the population during the initial phase of the COVID-19 pandemic.…”
mentioning
confidence: 99%
“…Naturally, the pandemic itself had an impact on the population's mental health, specifically through a high level of distress as a direct consequence of news [22] not to mention domestic violence and multiple domains of abuse needing adequate prevention problems [23].…”
Section: A Never-seen-before Scenario: Covid-19 Pandemicmentioning
confidence: 99%